Marketplace Responsibilities and Sanctions in Cases of Consumer Losses (Futuristic Legal Perspective) - Amaliya, Lia; Dewi, Sartika; Arafat, Zarisnov; Asyhadi, Farhan; Rosidawati , Imas (PT. Hafasy Dwi Nawasena, 2025)
Marketplace is a platform that has the task of acting as an intermediary between sellers and buyers to carry out the product transaction process online. Although from a business perspective it will benefit consumers, producers and the marketplace itself, from a legal perspective there will be many consequences that arise because there are no specific regulations governing this marketplace. Based on this, it raises the issue of whether the marketplace can be held legally responsible for consumer losses and how future laws can ensure that the marketplace is responsible for consumer losses that occur. With the normative legal method, the author analyzes laws and regulations, policy regulations, principles of e-commerce implementation, and principles of responsibility, which show that the marketplace platform as an electronic system organizer has legal responsibility in the event of losses to consumers. Conclusion Responsibility Related to the responsibility of business actors is regulated in Article 19 of Law No. 8 of 1999, while in Law Number 19 of 2016 in Article 15. And in Government Regulation Number 80 of 2019 it is regulated in Article 22 paragraphs (1) and (2). Although Indonesia already has regulations related to buying and selling through e-commerce platforms, their implementation is still considered ineffective in addressing consumer rights protection issues, so it is necessary to revise and harmonize inclusive laws and regulations, ensuring normative clarity and fairness in handling consumer rights violations in the marketplace.